A clinicopathological study of pulmonary mucormycosis in cancer patients: Extensive angioinvasion but limited inflammatory response - Ben-Ami, Ronen (J Infect, 2009)
OBJECTIVES: Pulmonary mucormycosis (PMM) is an emerging, frequently lethal fungal infection in immunosuppressed cancer patients. We sought to characterize the histopathologic features of PMM in this population. METHODS: We identified patients with PMM who underwent autopsy or lung biopsy between 1990 and 2007. Histopathology slides were blindly reviewed by a pathologist and findings were scored on standardized forms. Pathologic findings were correlated with demographic and clinical data abstracted from patient’s medical records. RESULTS: Twenty patients with PMM were included in this study. Nineteen patients (95%) had hematologic malignancies. High frequencies of angioinvasion (100%), hemorrhagic infarction (90%), coagulative necrosis (85%), and intra-alveolar hemorrhage (85%) were observed, whereas inflammatory infiltrates were uncommon (30%). Neutropenic patients had more extensive angioinvasion compared with non-neutropenic patients (77% versus 29%, P = 0.06). Allogeneic hematopoietic stem cell transplantation (HSCT) recipients, all of whom had graft-versus-host disease, had more inflammatory cell infiltration but less intra-alveolar hemorrhage than non-HSCT patients (67% versus 14%, P = 0.04; 50% versus 100%, P = 0.02, respectively). CONCLUSIONS: MM in immunocompromised cancer patients is characterized by extensive angioinvasion and coagulative necrosis. The different histopathologic features of PMM in neutropenic, non-neutropnic, and HSCT patients may reflect differences in the pathobiology of PMM in these populations.